EFEKTIVITAS LATIHAN HURDLE JUMP TERHADAP KEMAMPUAN DAYA LEDAK OTOT TUNGKAI PADA SISWA EKSTRAKURIKULER BOLA VOLI MA AL-IJTIHAD AL MAHSUNI LOMBOK TIMUR TAHUN 2018 - Susi Yundarwati; Isyani Isyani; Intan Primayanti (Gelora : Jurnal Pendidikan Olahraga dan Kesehatan IKIP Mataram, 2018)
The purpose of this study is to improve the ability of limb muscle explosive ability in MA Al-Ijtihad East Lombok Volleyball Extracurricular Students in 2018 through Hurdle Jump Training. To collect data using the documentation method and deed test method, the population study of this study was 10 volleyball extracurricular members of MA AL-Ijtihad. This study used the location of the volleyball court to practice and conduct tests. The method used in this study is the action test method, namely the Standing Broad Jump test and the hurdle jump exercise. Data analysis using t-test showed t-count was greater than t-table (2.684> 2.571), then hurdle Jump exercises were effective against increasing limb muscle explosive ability in Volleyball Extracurricular Students of MA Al-Ijtihad East Lombok 2018.